QARAQALPAQ TILIN OQÍTÍW METODIKASÍ BOYÍNShA IZERTLEWLER - Karamatdinova, Gawhar Tayırovna (SCIENCE and SOCIETY, 2026)
The article analyzes the history of formation and stages of development of Karakalpak language teaching methodology. The author studied the primary sources of Karakalpak language methodology, from the works of classical poets and thinkers to contemporary trends. Furthermore, issues of improving the methodology for learning word meanings and applying innovative technologies in teaching were discussed.